Governance of Banjar Song Socialization in Schools - Susyam Widiantho (International Conference on Science, Education, and Technology, 2023)
In the midst of globalization, technology, and the rapidly growing music industry, Banjar songs have started to lose their existence. This can be seen from the fact that many of the current generation, especially those living in urban areas, no longer recognize Banjar songs. Whereas in Lagu Banjar there is local wisdom and socio-cultural values whose presentation has even referred to the concept of Trikon Ki Hadjar Dewantara, but why has Lagu Banjar lost its existence even in the midst of its own "audience". Through conservative ideology, art education will provide space for individuals to develop self-confidence with their freedom. The approach to education in the arts through conservativism is more about the need to preserve and continue established artistic beliefs and practices. The purpose of this research is to provide ideas on how to manage the socialization of Lagu Banjar in schools where students are a strategic "link" in cultural inheritance. The method used is descriptive qualitative with an empirical phenomenological approach to obtain a comprehensive understanding, the description of which provides the basis for a reflective structural analysis that describes the governance of Lagu Banjar socialization in schools in the context of cultural preservation.